Functional analysis of the spatiotemporal distribution of the macrobenthos associated to bathylithological aspects and environmental variables at the Mackellar Inlet, King George Island, Antarctica - Moreno Leveroni, Bernabé (2017)
Trabajo presentado en el IX Congreso Latinoamericano de Ciencia Antártica. 4 al 6 de octubre de 2017, Punta Arenas-Chile. IX Latin American Congress on Antarctic Science.